2006
DOI: 10.2135/cropsci2006.01.0008
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance of Low Phytic Acid Wheat

Abstract: Low phytic acid (LPA) genotypes of wheat (Triticum aestivum L.) improve the nutritional quality of wheat by reducing the concentration of phytic acid (PA) in the aleurone layer, thus reducing the chelation of nutritionally important minerals and improving the bioavailability of phosphorus. Field studies were conducted at Aberdeen and Tetonia, ID, in 2003 and to evaluate the effects of the LPA genotype on the agronomic performance of wheat. These studies included wildtype (WT) and LPA genotypes in hard red spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 23 publications
(45 reference statements)
0
53
0
1
Order By: Relevance
“…Monogastric animals, such as poultry and swine, lack the ability to digest phytate, leaving significant amounts of phytate as the major organic P form in their excreta (Caldwell and Black 1958;He et al 2007, He andHoneycutt 2001;He et al 2006aHe et al , 2006bTurner 2004;Turner and Leytem 2004). Application of low-phytate grains (Bowen et al 2006;Guttieri, Peterson, and Souza 2006;Raboy et al 2000) and supplementation with phytase enzymes (Maguire et al 2004;Park, Choi, and Oh 1999) are two strategies to improve dietary availability of P in animal feedstuffs; however, these practices can result in more unpredictable phytate concentrations in animal manure and thus in the environment. A reliable and convenient analytical method is needed to identify and quantify phytate in animal manure.…”
Section: Introductionmentioning
confidence: 99%
“…Monogastric animals, such as poultry and swine, lack the ability to digest phytate, leaving significant amounts of phytate as the major organic P form in their excreta (Caldwell and Black 1958;He et al 2007, He andHoneycutt 2001;He et al 2006aHe et al , 2006bTurner 2004;Turner and Leytem 2004). Application of low-phytate grains (Bowen et al 2006;Guttieri, Peterson, and Souza 2006;Raboy et al 2000) and supplementation with phytase enzymes (Maguire et al 2004;Park, Choi, and Oh 1999) are two strategies to improve dietary availability of P in animal feedstuffs; however, these practices can result in more unpredictable phytate concentrations in animal manure and thus in the environment. A reliable and convenient analytical method is needed to identify and quantify phytate in animal manure.…”
Section: Introductionmentioning
confidence: 99%
“…Praćenje nasleđivanja analiziranjem F 2 i F 4:6 familija (Knežević et al 2008b) je utvrdilo da su u nastanak mutantnog fenotipa za nizak sadržaj fi tinske kiseline uključena dva gena. Guttieri et al (2006a) su izveli oglede 2003. i 2004. na dva lokaliteta koji su uključili WT i LPA genotipove jare pšenice: tvrdih i crvene boje zrna, tvrdih i bele boje zrna i mekih bele boje zrna. LPA genotipovi jarih sorata pšenice sa crvenom bojom zrna su imali zakasneli razvoj i redukovan prinos zrna za 8% do 25% u prinosnijoj sredini, delom zbog redukovane veličine zrna od 3 mg po zrnu.…”
Section: Genetička Varijabilnost Sadržaja Fi Tinske Kiseline Linija Iunclassified
“…Phytic acid and its salts are present at 0.5% to 5% (w/w) levels in edible legumes, cereal grains, oilseeds and nuts [5][6][7][8]. Genetic engineering and plant breeding efforts to reduce PA have resulted in the development of low PA (0.52 to 4.56 mg/g of phytic acid phosphorous) mutants in major cereal crops, such as maize (Zea mays L.), rice (Oryza sativa L.), wheat (Triticum aestivum L.), common bean (Phaseolus vulgaris L.), and barley (Hordeum vulgare L.) [9][10][11][12]. Animal studies have shown that substantial reductions in phytic acid levels in feed lead to improvements in calcium (Ca) and zinc (Zn) utilization [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy of colorimetric PA assays depends on the separation of different inositol isomers, assumptions of metal-color complexes, and chemical matrix interferences [17]. The colorimetry-based PA-P determination has been the method of choice for reporting the PA content of rice [10], field pea [18], wheat [9], soybean [12], maize [8], and common bean [19]. Therefore, the accuracy of the PA levels reported in these and many other studies is subject to the errors associated with the colorimetric procedures.…”
Section: Introductionmentioning
confidence: 99%